The prompter's hand book. - French, J. A. (Boston, O. Ditson Co., 1893)
Similar to other prompter's books published during the last half of the nineteenth century, French gives instructions for calling the figures of quadrilles including examples of how the calls correlate to the music. The book also covers the calling of contra dances (progressive figure dances performed by a column of men facing a column of women).
Available also through the Library of Congress Web site as facsimile page images and full text.
Keywords: Country dancing -- Handbooks, manuals, etc; Quadrille (Dance) -- Handbooks, manuals, etc; Dance Instruction and Technical Manuals; Prompting Quadrilles